Environmental Management in SD Alam Al Fath’s Bilingual Program: A Case Study - Failasofah Failasofah; Firman Afrian Pratama; Rofiazka Fahmi Huda; Sulhi Muhamad Daud Abdul Kadir (STAI Hubbulwathan Duri, 2024)
In the modern era, bilingual competencies not only enhance job opportunities and international collaboration but are also critical for effective environmental management in educational programs. Thus, environmental management of bilingual programs must be thoroughly examined and well-implemented. This article analyzes the policies and implementation of environmental management, along with influencing factors, at SD Alam Al Fath in Jambi City. The research employs a qualitative approach with a case study method developed from an interpretive paradigm. Through interviews, observations, documentation, and interactive analysis using Miles Huberman's approach, it is concluded that the environmental management of the bilingual program at SD Alam Al Fath in Jambi City is implemented through a well-structured series of daily, weekly, monthly, and yearly activities. There are five main supporting factors for these activities and three hindering factors: time constraints in the school environment, the lack of some supporting facilities, and various levels of language proficiency. This study suggests that student categorization can improve the effectiveness of bilingual programs in schools and similar programs elsewhere. However, if there is no possibility, inductive and expository strategies with direct and cooperative learning approaches could be preferred to improve the Arabic and English language proficiency of heterogeneous learners.